Practice of banking : volume 1 - Adekanye, Femi. (Marina, Lagos : Collins, F & A publishers ltd, 1986)
The book is divided into two parts. It opens with a short introductory chapter dealing with a historical sketch on Nigerian banking. Part B adequately covers securities for bankers' advances in Nigeria.
Includes index
osc 10/05/17
Loans
Keywords: Banking Services; Banking Practice